2020
DOI: 10.3389/fcell.2020.00375
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of Transcription Programs in Adult Stem Cell-Derived Jejunum Organoids and Original Tissue During Long-Term Culture

Abstract: The emergence of intestinal organoids, as a stem cell-based self-renewable model system, has led to many studies on intestinal development and cell-cell signaling. However, potential issues regarding the phenotypic stability and reproducibility of the methodology during culture still needs to be addressed for different organoids. Here we investigated the transcriptomes of jejunum organoids derived from the same pig as well as batch-to-batch variation of organoids derived from different pigs over longterm passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 49 publications
3
41
1
1
Order By: Relevance
“…The objective of intestinal organoid cultures is to replicate in vitro as closely as possible the phenotype of the intestinal epithelium observed in vivo. Transcriptome analysis revealed that pig jejunum organoids resembled more pig jejunum tissue than the pig IPEC-J2 cell line [ 5 ]. For instance, genes coding for enterohormones or mucins were similarly expressed in jejunum tissue and organoids while they were not expressed in IPEC-J2, probably because of the lack of cellular diversity in this cell line [ 5 ].…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
See 4 more Smart Citations
“…The objective of intestinal organoid cultures is to replicate in vitro as closely as possible the phenotype of the intestinal epithelium observed in vivo. Transcriptome analysis revealed that pig jejunum organoids resembled more pig jejunum tissue than the pig IPEC-J2 cell line [ 5 ]. For instance, genes coding for enterohormones or mucins were similarly expressed in jejunum tissue and organoids while they were not expressed in IPEC-J2, probably because of the lack of cellular diversity in this cell line [ 5 ].…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
“…Transcriptome analysis revealed that pig jejunum organoids resembled more pig jejunum tissue than the pig IPEC-J2 cell line [ 5 ]. For instance, genes coding for enterohormones or mucins were similarly expressed in jejunum tissue and organoids while they were not expressed in IPEC-J2, probably because of the lack of cellular diversity in this cell line [ 5 ]. Gene expression patterns also largely overlapped between bovine epithelial crypts and enteroids [ 22 ].…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
See 3 more Smart Citations